การเสริมพลังศักยภาพผู้นำชุมชนเพื่อการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียง พื้นที่ตำบลรังกาใหญ่ อำเภอพิมาย จังหวัดนครราชสีมา - Loetyingyot, Siriporn; Phultawee, Wipawee; dejtano, Isari (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 4 (2561): October-November 2018, 2018)
การศึกษามีวัตถุประสงค์เพื่อ 1) ศึกษาแนวทางดำเนินงานการเสริมพลังศักยภาพผู้นำชุมชนเพื่อการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียง 2) ดำเนินการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงผ่านการดำเนินงานการเสริมพลังศักยภาพผู้นำชุมชนเพื่อการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงโดยการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม 3) เสริมข้อมูลและการเรียนรู้ตอบสนองการดำเนินงานขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงแบบองค์รวม เป็นกระบวนการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม และผู้ให้ข้อมูลหลักคือ ผู้นำชุมชน 20 หมู่บ้านและ เจ้าหน้าที่เทศบาลตำบลรังกาใหญ่ เพื่อค้นหาบริบทผู้นำชุมชนและศักยภาพผู้นำชุมชน ค้นหาแนวทางเสริมพลังศักยภาพผู้นำชุมชน ติดตามการดำเนินงานเพื่อให้การขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงเป็นไปอย่างต่อเนื่อง      ผลการวิจัย พบว่า 1) ผู้นำชุมชนส่วนใหญ่ประกอบอาชีพเกษตรกรรม สำหรับความคิดเห็นของคนในชุมชนเกี่ยวกับศักยภาพของผู้นำชุมชนด้านคุณลักษณะของผู้นำและด้านการปฏิบัติตามบทบาทของผู้นำตามหลักปรัชญาเศรษฐกิจพอเพียงอยู่ในระดับมาก 2) การดำเนินการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงผ่านการเสริมพลังศักยภาพผู้นำชุมชน พบว่า ผู้นำชุมชนเกิดการปรับเปลี่ยนกระบวนทัศน์และได้แนวทางการประยุกต์ใช้พัฒนาชุมชนตามหลักปรัชญาเศรษฐกิจพอเพียง 3) การเสริมข้อมูลและเรียนรู้การตอบสนองการดำเนินงานขับเคลื่อนปรัชญาเศรษฐกิจพอเพียงแบบองค์รวม พบว่า ผู้นำเกิดการต่อยอดองค์ความรู้ในกระบวนการขับเคลื่อนปรัชญาเศรษฐกิจพอเพียง นำไปสู่การพัฒนาศักยภาพชุมชนให้เกิดทักษะการเรียนรู้และสามารถใช้ชีวิตบนพื้นฐานการพึ่งพาตนเองอย่างเข้มแข็ง คำสำคัญ : การเสริมพลังศักยภาพ  ปรัชญาเศรษฐกิจพอเพียง  ผู้นำชุมชน      The objectives of this study were: 1) to investigate guidelines for enhancing community leaders’ potential for steering the Sufficiency Economy Philosophy; 2) to enhance community leaders’ potential using participatory action research; and 3) to support information and learning related to the holistic steering of Sufficiency Economy Philosophy. The study employed the participatory action research and key informant were 20 community leaders and officials at Rang Ka Yai Sub-district. The study aimed to find guidelines for the community leaders for steering the Sufficiency Economy Philosophy through to the follow-up for providing information on the leaders’ continuing actions within the community.      The study showed the following results: 1) The majority of the community leaders had their occupation in agriculture. For the community leader potential in terms of leader characteristics and performance as the leaders’ roles according to the sufficiency economy philosophy was perceived by the people in the community at the high level. 2) The operation of steering the sufficiency economy philosophy, the results showed that community leaders, made changes in their paradigm and implemented the guidelines to improve the community. 3) Results on the support of information and learning related to the holistic steering of Sufficiency Economy Philosophy found that the leaders forwarded knowledge in the process of steering the Sufficiency Economy Philosophy which leaded to the development of the community potential of learning skills and the ability lives based on the strong self-dependency. Keywords: Enhancing Potential, Sufficiency Economy Philosophy, Community Leaders’